07 Characteristics of Application of General Didactic Principles to the Specificity of Tactical, Operational and Strategic Military Higher Education - Paul-Claudiu COTÎRLEŢ (Association of Social and Educational Innovation, 2015)
The paper entitled "Characteristics of Application of General Didactic Principles to the Specificity of Tactical, Operational and Strategic Military Higher Education" wants to develop the educational and instructive character of all teaching activities, and to ensure the achievment of objectives provided in the millitary education programmes. It covers three sections and four subchapters, all of them dealing with notions, principles, rules and examples that will help with the methodical preparation of young teachers. If studied and applied in a creative way, the thesis will provide a scientific background and it will ease the work done by both the teachers and the studentofficers. Also, this paper tries to answer to a desire regarding tactical, strategic and operative education that concerns the synthesizing, systematization and generalization of the positive experience coming from teachers and teaching committees. Seeing as this is a first attempt to present such particularities, I would like to state that the thesis in question is open to changes and improvements, and also I would be grateful for any suggestions or observations from the people that study or use this paper, in order to improve the teaching of such an important and specific learning process.